Integrasi Sistem Informasi Penyelesaian Tugas Akhir dan Sistem Informasi Praktek Kerja Lapangan Berbasis REST API Pada Program Studi DIII Teknik Informatika Politeknik Negeri Pontianak - Lindung Siswanto; Tommi Suryanto; Ir. Suharto; Muhammad Ridhwan Sufandi (Jurnal ELIT, 2023)
The application of technology in solving problems has a positive impact, one of which is in the problem of completing the final project and field work practices where these two processes have been able to run well accompanied by an information system, which for the completion of the final project is assisted by SEMESTA (Completion Information System). Final Project) and for the Field Work Practice assisted by SIMPKL (Field Job Training Information System), but in its development there are new problems that occur after the implementation of this information system, where the system that runs separately causes data from both information systems to be inaccurate , and because in the process of implementing TA and PKL there is a designated coordinator from the Head of Study Program who uses this information system, a gap appears where the data processed at SIMPKL cannot be forwarded or continued to SEMESTA, so the TA coordinator must carry out i enter data again where the data is not the same as the one in SIMPKL. From these problems, it is necessary to take steps to solve the problem, namely by integrating the final project completion information system and the field work practice information system which will be connected using the REST API. The results of this integration are expected to be able to make the process of completing the Final Project and the implementation of the Field Work Practice systematic and make it easier for the coordinator to check the data of students who have completed street vendors or not, so that the data can be directly accessed at SEMESTA